Developing the National Modernist Pattern: Three Plays by Igor Kostetsky - Yuri Y. Barabash (Studia Litterarum)
The article analyzes three plays written by Igor Kostetsky (1945–1947) in a) hermeneutic, comparative, and historical perspectives and b) in Ukrainian and European literary contexts. In the play Temptation of Non-Saint Anton, absurd becomes a meaning-making factor that allows us to compare this play with European absurd theatre (Adamov, Beckett and Ionesko). In the plays Twins will Finally Meet and Drama of a Great Man, other trends prevail, absurdist elements notwithstanding. These trends include the following aspects: psychological themes (Doppelganger motif, mythological archetypes), ideological and moral issues (discussions whether violence is acceptable as а means to achieve a noble goal), philosophical and religious attitudes (irrational nature of Power, its mystery component, zombification of the masses). Typological similarity of the analyzed works relies on the modernist paradigm as well as on the modernist aesthetics including the violation of cause and effect, temporal and spatial deviations, transformation of archetypical images and sacred figures, elements of medieval and baroque stylizations, intertextuality etc. These peculiarities become manifest when the plays by Kostetsky are compared with Flaubert’s interpretation of St. Anthony’s legend, Doppelganger motif in Gogol and Shevchenko, Dostoevsky and Andrey Bely, mystery component in Lorca and T.S. Eliot. Plays and the main prosaic works by Kostetsky as well as his literary heritage as a whole represent the connecting link between Ukrainian Modernism of the 1920s (“Executed Renaissance”) on the one hand and modernist and post-modernist trends in modern Ukrainian literature on the other, being a significant stage in the development of the national modernist pattern.